2018
DOI: 10.1172/jci.insight.99694
|View full text |Cite
|
Sign up to set email alerts
|

Guaiacol as a drug candidate for treating adult polyglucosan body disease

Abstract: Adult polyglucosan body disease (APBD) is a late-onset disease caused by intracellular accumulation of polyglucosan bodies, formed due to glycogen-branching enzyme (GBE) deficiency. To find a treatment for APBD, we screened 1,700 FDA-approved compounds in fibroblasts derived from APBD-modeling GBE1-knockin mice. Capitalizing on fluorescent periodic acid-Schiff reagent, which interacts with polyglucosans in the cell, this screen discovered that the flavoring agent guaiacol can lower polyglucosans, a result also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 29 publications
0
43
0
Order By: Relevance
“…As PB quantity was not compared before and after treatment, it remains unclear whether the observed difference in PB quantity was exclusively due to treatment-dependent halting of PB formation or whether some form of polyglucosan degradation occurred. Nevertheless, it was shown that, in cell culture, guaiacol treatment was able to reduce glycogen that was deemed amylase resistant under the experimental conditions (Solmesky et al, 2017; Kakhlon et al, 2018). Whether this effect is attributable exclusively to GYS1 inhibition remains to be determined.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As PB quantity was not compared before and after treatment, it remains unclear whether the observed difference in PB quantity was exclusively due to treatment-dependent halting of PB formation or whether some form of polyglucosan degradation occurred. Nevertheless, it was shown that, in cell culture, guaiacol treatment was able to reduce glycogen that was deemed amylase resistant under the experimental conditions (Solmesky et al, 2017; Kakhlon et al, 2018). Whether this effect is attributable exclusively to GYS1 inhibition remains to be determined.…”
Section: Resultsmentioning
confidence: 98%
“…Treatment approaches aiming at lowering GYS1 activity globally would include a reduced formation of at risk sites as elongation:branching ratio is generally decreased. For instance, Gbe1 ys/ys mice treated for 12 months with GYS1 inhibitor guaiacol showed reduced polyglucosan bodies when compared to untreated animals (Kakhlon et al, 2018). As PB quantity was not compared before and after treatment, it remains unclear whether the observed difference in PB quantity was exclusively due to treatment-dependent halting of PB formation or whether some form of polyglucosan degradation occurred.…”
Section: Resultsmentioning
confidence: 99%
“…The anticipated safety profile of GYS1 knockdown is furthermore favorable as humans with one null GYS1 allele are healthy 34 . GYS1 could be downregulated at the DNA, RNA, or protein levels, and progress is already being made at least in the latter with promising compounds including guaiacol 35 and imidazole analogs 36 . PPP1R3C deficiency has to date not been associated with a pathological state in humans.…”
Section: Discussionmentioning
confidence: 99%
“…As in muscle, a pre-extraction incubation as devised removes all soluble and non-inert glycogen, revealing a very robust difference between diseased and WT animals already at a young age. As studies in young mice can be completed faster and therefore present a smaller financial burden, this method will be beneficial in studies assessing efficacy of therapeutic approaches for prevention or removal of insoluble brain glycogen, such as in LD (10,31) or adult polyglucosan body disease (41). The sensitivity of the described method is sufficient to determine inert αglucans in pieces of mouse brain weighing less than 20 mg, e.g.…”
Section: Quantification Of Inert α-Glucans In Hippocampi Of Ld Micementioning
confidence: 99%
“…Monitoring glycogen synthesis in human cell culture is crucial in any therapeutic study targeting central enzymes of glycogen metabolism. For instance, glycogen synthase has been identified a therapeutic target in LD (13,43,44) and adult polyglucosan body disease (41).…”
Section: Quantification Of α-Glucans In Hek293 Cells Cultured In 96 Wmentioning
confidence: 99%